2016
DOI: 10.1016/j.ydbio.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-B receptor deficiency causes cerebral vasculature defects during embryonic development in mice

Abstract: Nogo-B receptor (NgBR) was identified as a receptor specific for Nogo-B. Our previous work has shown that Nogo-B and its receptor (NgBR) are essential for chemotaxis and morphogenesis of endothelial cells in vitro and intersomitic vessel formation via Akt pathway in zebrafish. Here, we further demonstrated the roles of NgBR in regulating vasculature development in mouse embryo and primitive blood vessel formation in embryoid body culture systems, respectively. Our results showed that NgBR homozygous knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Immunohistochemistry was performed as described [17]. In brief, paraffin sections were deparaffinized in xylene and rehydrated in decreasing concentration of ethanol solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed as described [17]. In brief, paraffin sections were deparaffinized in xylene and rehydrated in decreasing concentration of ethanol solutions.…”
Section: Methodsmentioning
confidence: 99%
“…NgBR was identified as a Nogo-B receptor specific for the amino terminus of Nogo-B (AmNogo-B). NgBR is necessary for angiogenesis by mediating chemotaxis of endothelial cells [ 12 ], and is essential for vasculature development [ 13 , 14 ]. Our recent findings demonstrated that NgBR binds farnesylated Ras and recruits Ras to the plasma membrane, which is a critical step required for receptor tyrosine kinase (RTK)-mediated activation of Ras signaling in human breast cancer cells and tumorigenesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates an important role for Nogo-B receptor (NgBR) signaling and the expression level of this receptor in angiogenesis ( 10 13 ). NgBR is a transmembrane receptor protein that has been identified as a Nogo-B-binding protein and is essential for the Nogo-B-mediated chemotaxis of ECs and their organization into tubes ( 10 ).…”
Section: Introductionmentioning
confidence: 99%